A stranger's supper an oral history of Centenarian women in Montenegro - Milich, Zorka (New York : London : Twayne Publishers ; Prentice Hall, 1995)
"Men are fighters. Who would protect us? Everything else has to be taken care of for them. That is what women are for." So says Milena, one of ten women one hundred years old or more who in this oral history offer a rare look inside the traditional tribal culture of Montenegro. Interviewed by Zorka Milich, herself a descendant of Montenegrins and a fluent speaker of their Serbian language, these articulate centenarians explain what life was like for the women behind Montenegro's warriors.; Milich's ease with the women of the country of her parents' birth makes possible intimate and lively conversation where shyness and reserve with outsiders are the norm. They talk about their relationship with their husbands, their experience of childbirth (which women often underwent outdoors or in a barn, sometimes alone), the pain of losing a son to war and not being able to grieve openly (pride that he gave his life for Montenegro was the "correct" response).; And they give eyewitness accounts of historic events - the Balkan Wars, World War I, and World War II - as they played themselves out in this remote and barren country the Montenegrins call Crna Gora, or Black Mountain.
Includes bibliographical references (p. 151-153) and index.
74352
Keywords: Women -- Interviews -- Yugoslavia -- Montenegro; Centenarians -- Interviews -- Yugoslavia -- Montenegro; Oral biography; Montenegro -- Social life and customs; Montenegro -- History